2018
DOI: 10.1108/heswbl-10-2017-0076
|View full text |Cite
|
Sign up to set email alerts
|

Promoting interdisciplinarity through an intensive entrepreneurship education post-graduate workshop

Abstract: Purpose While creativity and innovation are found within many disciplines, the opportunity to develop a tangible skill set and share ideas with contemporaries can be limited within the siloed structure of many tertiary institutions. The purpose of this paper is to evaluate a model that addresses the pedagogical challenge of interdisciplinary learning. Design/methodology/approach This paper adopts a case-based approach. The case subject is Aalborg University that founded an intensive entrepreneurial education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
(18 reference statements)
0
5
0
1
Order By: Relevance
“…It is likely to have a positive impact if other relevant disciplines are linked to the entrepreneurship sub-topic as part of the curriculum. This would provide the program with a scientific context, enhance career relevance (Bridgstock, 2013), and facilitate finding solutions to complex problems (McDonald et al, 2018). Entrepreneurship is also a dynamic study with a history of being related to many variables such as knowledge and experience (Gupta et al, 2016), being very contextual (Thomassen et al, 2019), and comprehensive in nature (Hägg and Kurczewska, 2019).…”
Section: Literature Review Social Values Shaping Student Entrepreneur...mentioning
confidence: 99%
“…It is likely to have a positive impact if other relevant disciplines are linked to the entrepreneurship sub-topic as part of the curriculum. This would provide the program with a scientific context, enhance career relevance (Bridgstock, 2013), and facilitate finding solutions to complex problems (McDonald et al, 2018). Entrepreneurship is also a dynamic study with a history of being related to many variables such as knowledge and experience (Gupta et al, 2016), being very contextual (Thomassen et al, 2019), and comprehensive in nature (Hägg and Kurczewska, 2019).…”
Section: Literature Review Social Values Shaping Student Entrepreneur...mentioning
confidence: 99%
“…Universities should focus more on creating a cross-disciplinary approach to entrepreneurial learning to develop and foster the skills needed to create successful entrepreneurs. Entrepreneurship education should be encouraged in an interdisciplinary approach (McDonald et al. , 2018) as entrepreneurship is context dependant (Wasim et al ., 2022b).…”
Section: Discussionmentioning
confidence: 99%
“…Universities should focus more on creating a cross-disciplinary approach to entrepreneurial learning to develop and foster the skills needed to create successful entrepreneurs. Entrepreneurship education should be encouraged in an interdisciplinary approach (McDonald et al, 2018) as entrepreneurship is context dependant (Wasim et al, 2022b). At the end of the day, not only business students are those starting-up a business, there are others from non-business disciplines who also have this mindset but may require more discipline and certain skills to be developed.…”
Section: Intentions Of Becoming An Entrepreneurmentioning
confidence: 99%
“…The results indicated that there is a minor positive recalibration of students' perceptions in the areas of course relevance and opportunities for outside interests during the first months of year one [30]. Some studies proposed the education efficiency between input and output based on data envelopment analysis [31] and fuzzy DEA methods [32], [33]. Long Short-Term Memory approach, one of deep learning methods, was used to forecast the learners' motivation and participation in the learning process [34].…”
Section: The Question Of Estimating Efficiency In Interdisciplinary S...mentioning
confidence: 99%